2016
DOI: 10.1111/sjop.12325
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of coping strategies in patients with fibromyalgia, chronic neuropathic pain, and pain‐free controls

Abstract: Patients suffering from chronic pain may benefit from learning adaptive coping strategies. Consensus on efficient strategies for this group of patients is, however, lacking, and previous studies have shown inconsistent results. The present study has examined coping strategies in two distinctly different groups of chronic pain patients and a group of healthy controls. Thirty neuropathic pain (NP) patients, 28 fibromyalgia (FM) patients, and 26 pain-free healthy controls completed the Coping Strategy Questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 46 publications
3
23
0
2
Order By: Relevance
“…These findings are similar to previous research that studied women diagnosed with FM, which found that FM patients reported more severe symptoms of depression, anxiety, insomnia and fatigue than controls, which constitute typical bodily and mental symptoms accompanying FM pain [32]. Elevated levels of pain catastrophizing and negative affect have also been previously observed [33][34][35][36].…”
Section: Discussionsupporting
confidence: 90%
“…These findings are similar to previous research that studied women diagnosed with FM, which found that FM patients reported more severe symptoms of depression, anxiety, insomnia and fatigue than controls, which constitute typical bodily and mental symptoms accompanying FM pain [32]. Elevated levels of pain catastrophizing and negative affect have also been previously observed [33][34][35][36].…”
Section: Discussionsupporting
confidence: 90%
“…In the applied questionnaires FMS patients reported more severe symptoms of depression, anxiety, insomnia and fatigue than controls, which constitute typical bodily and mental symptoms accompanying FMS pain ( Wolfe et al, 2010 ). Elevated levels of alexithymia, pain catastrophizing and negative affect, and the reductions in positive affect and self-esteem, have also been previously observed ( Michielsen et al, 2006 ; Hassett et al, 2008 ; Garaigordobil, 2013 ; Montoro et al, 2015 , 2016 ; Baastrup et al, 2016 ). The latter results confirm the view of emotional impairment as a crucial aspect of FMS pathology ( Weiss et al, 2013 ; Rosselló et al, 2015 ; Montoro et al, 2016 ).…”
Section: Discussionmentioning
confidence: 56%
“…Several studies revealed markedly increased levels of alexithymia in FMS and its expression is associated with pain severity, disability and reduced quality of life ( Castelli et al, 2012 ; Martínez et al, 2014 ; Montoro et al, 2016 ). In addition, the maladaptive coping strategy of pain catastrophizing is believed to play a key role in FMS pathology ( Gracely et al, 2004 ; Baastrup et al, 2016 ). Pain catastrophizing, defined as an exaggerated negative orientation to pain, is an important source of fear and discomfort, which in turn may increase pain perception ( Severeijns et al, 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Coping signifies purposeful cognitive and behavioural efforts to overrule the negative impact of stress (Lazarus, ). A growing consensus supports the significance of pain coping in the understanding of prolonged pain in children (Reid et al., ; Thastum et al., ; Bandell‐Hoekstra et al., ; Hermann et al., ; Claar et al., ; Huguet et al., ; Ostlie et al., ; Kashikar‐Zuck et al., ; Simons et al., ; Agoston et al., ; Baastrup et al., ; Gaultney et al., ). To measure pain coping is to distinguish the ongoing cognitive, behavioural and emotional processes connected to pain in children and adolescents with recurrent or chronic pain.…”
Section: Introductionmentioning
confidence: 98%